Isolation and molecular diagnosis of lactic acid bacteria in intestine of Siberian sturgeon (Acipenser baerii) - Shenavar Masouleh, A.; Pourkazemi, M.; Soltani, M.; Yarmohammadi, M.; Yazdani, M.; Alizadeh, M.; Jalilpour, J.; Bazari Moghaddam, S.; Masoumzadeh, M.; Hoseynifar, S.H.; Esmaeilii, P.; Baniesmaeilii, Y. (2018)
Caspian Sea sturgeons, are the most valuable species due to the production of meat and caviar. Sturgeon cultures as like other fish rearing, the outbreak of all kinds of infectious diseases in the farms can be expected and in this regard, isolation, identification and consumption of the local probiotics can be very important in the health promotion and growth indices. For this purpose, sampling has been done from 38 fish, in addition to culturing and counting aerobic and facultative anaerobic bacteria (AFAB) on Triptic Soy Agar, and lactic acid bacteria (LAB) were also isolated and counted on MRS Agar. In Siberian sturgeon, the average number of LAB were 2.72±0.11 (Log CFU g-1 ) and the average of AFAB were 6.79±0.19 (Log CFU g-1 ). Through 16SrRNA gene sequencing, LAB including Weissella confusa, Lactococcus lactis, and L. garvieae were molecular identified in the Siberian sturgeon intestines. Complete laboratory and field studies for use of these bacteria as probiotics is required. Published